Peranan Penting Evaluasi Pembelajaran pada Menulis Permulaan - Magdalena, Ina; Ramdhan, Ananda Sinta; Zaudah, Dessiana; Azizah, Nur (Lembaga Yasin AlSys, 2023)
Evaluation is part of the assessment on each subject. Evaluation carried out on an ongoing basis will allow the assessor to assess the extent to which the program is being developed to achieve the goals that have been designed. Beginning writing is the ability to write that is taught to students in the early stages, namely in grades I and II, with this ability students are expected to be able to express their thoughts and feelings accompanied by by writing. This type of research is descriptive with a quantitative approach. In this research is expected to be able to describe the real situation in the field. According to Mukhtar (2013.10) the descriptive-quantitative method is a method used by researchers to find knowledge or theories about this researcher using a qualitative descriptive method. By collecting data, observation and in-depth interviews. Based on the results of evaluation research on learning to start writing at SD Negeri Mekarsari 1 Rajeg Using evaluation, which consists of several tests and non-tests (formative) as well as tests and non-tests (summative), and the results of the discussion of one of the teachers at SD Negen 1 Rajeg, Behau uses several steps in conducting evaluation of initial writing, namely, 1 Implement tests, both tests and non-tests, in the evaluation process chain the teacher must make a learning evaluation, the evaluation process can be completed by carrying out tests or tests, which can occur at the beginning, middle or end of the learning process in one semester. There are four basic language skills that must be possessed by every student, namely listening ability, speaking ability, seeing ability, and writing ability. The purpose of writing the beginning has the goal of teaching and training.